Psychoeducation group counselling for emotional intelligence among secondary school female students - Ummur Radhiah Hussin; Zuria Mahmud; Dharatun Nissa Fuad Mohd Karim (Journal of Counseling, Education and Society, 2020)
Students who have difficulties understanding and managing their emotions are also potentially challenged in organizing other aspects of their life such as academics performance and peer relationships. This article reports on a psycho-educational intervention for a group of 19 female students (age 15 to 16 years old) at a secondary school to help them improve their knowledge and skills in controlling their emotions in a more effective way. The students were involved in five psychoeducational group counselling sessions, which lasted between 40 to 45 minutes each session. The module for this intervention contained group counselling, creative activities (drawing, balloon blowing) and answering checklists (emotional stability). The emotional stability checklist showed that participants who scored low on anxiety and depression showed good responses and were engaged in the discussion. Meanwhile, students who scored high on anxiety, low self-esteem, and depression were less involved. However, the activities enabled students to know their friends better, enabled students feel more comfortable to share about themselves, able to understand beyond basic emotions and feel more empowered in controlling their emotions. This study supports the use of counseling group psychoeducation activities in providing quality programs for helping adolescents understand and manage their emotions.